Engineering drawing - Boundy, A. W. (Albert William) (McGraw-Hill, 2012)
Engineering Drawing remains the leading Australian text for students of engineering drawing and graphics. Building on Bert Boundy's meticulous and reliable approach to his subject, you will find: additional material and more chapters than before; better chapter organisation; expansion of the CAD corner feature; question banks; problems; the most commonly used reference tables.